SYLWETKA ABSOLWENTA FILOLOGII GERMAŃSKIEJ O SPECJALNOŚCI NAUCZYCIELSKIEJ A RZECZYWISTY STAN PRZYGOTOWANIA KANDYDATÓW DO ZAWODU NAUCZYCIELA - Mihułka, Krystyna (Neofilolog, 2019)
The article presents and discusses the results of a questionnaire conducted among third-year undergraduate students and second-year graduate students of German Philology at the University of Rzeszów taking the specialization in the teaching of German. The aim of the questionnaire was to draw attention to and assess the current state of the students’ preparation for work in the teaching profession. Analysis of the results reveals to what extent the programme of studies in the Department of German Philology, particularly within the teaching specialization, fulfils the students’ expectations. In addition, the respondents’ proposals concerning how the quality of teacher education in the Department of Ger-man Philology could be improved are presented and discussed by the author.